Gambaran Tren Program Pembangunan Keluarga Kelompok Kegiatan Bina Keluarga Balita (Poktan BKB) (Survei KKBPK RPJMN Keluarga 2017) - Aftina Eka Rahmayanti; Nurul Fitriyah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
Being the main pilar of development, there is still a need to develop the qualities of human resource. These qualities of human resources consist of level of health and emotional and spiritual maturities that can be assessed from a child starting from the fetus stage to the age of 6 years old. During this period, a child is in a serious need of nutritious and balanced food, education, and care for various aspects so that her or she can grow and develop optimally through a good family development. The aim of this research was to describe family development program trends throughout the so-called activity group of Bina Keluarga Balita (BKB). Hence, this study used the descriptive quantitative approach. The data were collected from the results of the KKBPK survey on 2017 family RPJMN. The results howed that family knowledge on BKB increased by 43% (in 2017) compared to 41% (in 2016), family parenting experiences in the nurturing children who where under five-years of age and of pre-school ages mostly consisted of distribution of nutritious food, amounting to 72.9% (2015), 70.8% (2016) and 73.4% (2017), accompanying children to play which reached 39.25% (2015), 57.2% (2016) and 63.5% (2017), and giving the opportunity to their children to play with their peers which amounted to 52.2% (2015), 72.0% (2016) and 78.0% (2017). In conclusion, family development trends through the Bina Keluarga Balita activity group showed an increased from year 2015 to 2017. Moreover, the index of parenting experiences and growth and development of children under five years of age and of pre-school ages was 66.7% in year 2017 (index range 0–100), which had fulfilled the strategic planning target.